If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -25 = -6x + 30 Reorder the terms: -25 + -1x = -6x + 30 Reorder the terms: -25 + -1x = 30 + -6x Solving -25 + -1x = 30 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -25 + -1x + 6x = 30 + -6x + 6x Combine like terms: -1x + 6x = 5x -25 + 5x = 30 + -6x + 6x Combine like terms: -6x + 6x = 0 -25 + 5x = 30 + 0 -25 + 5x = 30 Add '25' to each side of the equation. -25 + 25 + 5x = 30 + 25 Combine like terms: -25 + 25 = 0 0 + 5x = 30 + 25 5x = 30 + 25 Combine like terms: 30 + 25 = 55 5x = 55 Divide each side by '5'. x = 11 Simplifying x = 11
| x^2+13x+6=0 | | 30p=516 | | x^3-21x+20=0 | | -x+6=8x-3 | | -x-25=-6+30 | | -108=-6n-3(-8n+6) | | -0.10(19)+0.45=0.05(x-6) | | 6(c-7)=-18 | | -15(2x-7)+24=89 | | 3y+4=5y+6 | | 7.7(x-4)=-0.3x+25.2 | | 5[2(3x-3)-4(2x-3)]=3x+17 | | 90=2l+2w | | 4(x-5)+6=2(x-5) | | 5(2x-3)=2(x-2)+5 | | 2X^2-11X-6=0 | | 10y-13=3y+8 | | -3z=12 | | 7(4x+6)=-126 | | 2x*2+21x-11=0 | | f=3x^2-26x+48 | | 8n+5=6n-3 | | 3a+4-a+2=10 | | g(x)=7x-14 | | 6+7y=48 | | .8333333333+.2x=.666666667 | | 13+11x=68 | | 2x+9x=11x | | 6x^2-16x+7=0 | | -4.3=0.7-5y | | 6x-2=3(x+1)+1 | | 4x-90=-6x+40 |